Cow's Milk Protein-Sensitive Enteropathy (CMPSE) in Infant With Chronic Diarrhea - Sutjiningsih Sutjiningsih; Pitono Soeparto; Harsono Salim; Daniel Hardjadinata; Liek Djupri (Paediatrica Indonesiana, 1982)
Six cases of CMPSE as revealed by biopsy studies and clinical symptoms are presented. All infants suffered from chronic diarrhea, of which 5 developed failure to thrive.No pathogenic microorganism was isolated from the stools. Stool ova and parasites were also negative. Lactose intolerance was not found among these infants. The possible pathogenesls has been briefly discussed. The present series obviously indicates that CMPSE does occur in Indonesia.